UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETIL ASETAT DAUN WUNGU (Graptophyllum pictum (Linn) Griff) DENGAN METODE FRAP (FERRIC REDUCING ANTIOXIDANT POWER) - Aminah Aminah; A. Muflihunna; Zainal Abidin (Fakultas Farmasi UMI, 2016)
‘Wungu’ leaf is a plant known to contain flavonoids as the antioxidant. Thisresearch aimed to determine the antioxidant activit ethyl acetace fraction of ‘Wungu’ leaf (Graptophyllum pictum (Linn) Griff) by Ferric Reducing Antioxidants Power (FRAP) method. Extraction by maceration method usingethanol 96 %. Extract partitioned with ethyl acetace and water. Thefiltrate was dried with rotary evaporator and produce ethyl acetace fraction.Fraction were analyzed quantitatively by FRAP method with potassium ferriccyanide reagent solution, phosphate buffer, ferricchloride and distillede water. The sampel solutions analyzed by UV-vis spectrophotometer at a maximum wavelength of 705 nm using kuarsetin solution as a standard. The result showed that the antioxidantactivity of ethyl acetate fraction of ‘wungu’(Graptophyllum pictum (Linn) Griff) is3.984x10-6 g QE/g fraction.